The role of endotoxin receptors toll-like receptor 4 and lipopolysaccharide-binding protein in Mycobacterium tuberculosis infection - Abel, Brain (Division of Immunology, 2017)
The aim of this study was to investigate the role of PRRs, namely TLR4 and LBP in vivo in the development of an immune response to a Mycobacterium tuberculosis infection. Mice with null mutations of the endotoxin receptors LBP and TLR4 were compared with wild-type mice (PRRs intact) in the context of an aerosol Mtb infection. The following questions were posed: Are the PRR-disrupted animals more susceptible to M.tuberculosis infection? What role do these PRRs play in inflammatory processes and in the development of granuloma? What role do the PRRs play in driving cytokine and chemokine response? Specifically, the following mice were infected aerogenically with Mtb H37Rv to further investigate their roles in vivo in mounting an effective immune response: C3H/HeN and C3H/ HeJ (TLR4 mutant) LBP+/+ and LBP-/-